Festival Anak Soleh sebagai Strategi Internalisasi Nilai Moderasi Beragama pada Generasi Muda di Desa Sihuik-huik, Kec. Angkola Selatan - Abdurrahman Nafis; Amnah Faridah Hasibuan; Nurul Khaidah; Inna Muthmainnah Dalimunthe; Abdul Gani Jamora Nasution (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Religious moderation is a strategic agenda in strengthening national and state life amidst diversity. Moderation values ​​such as tolerance, sportsmanship, peace-loving, and respect for differences need to be instilled from an early age to become part of the character of the younger generation. The Pious Children Festival activity carried out through the Real Work Lecture (KKN) program in Sihuik-huik Village, South Angkola District was designed as an effort to internalize the value of religious moderation. This study used a descriptive qualitative approach with a participatory action research method through observation, documentation, and interviews. The results of the activity showed that the Pious Children Festival was able to be an effective medium in instilling the value of religious moderation through five main strategies: (1) educational, namely instilling moderate understanding through religious-themed competitions; (2) role model, by presenting fair committees and judges; (3) habituation, through the practice of sportsmanship and togetherness; (4) participatory, by involving children, parents, and the community; and (5) recreational, by presenting a fun competition atmosphere. Thus, the Pious Children Festival has been proven to not only strengthen children's religiosity, but also shape moderate characters that are in accordance with the principles of religious moderation.